Shrinking Cities for Economic Growth? Insights From the Housing Sector - Ferreira, António (2024)
This research focuses on examining how the pursuit of economic growth can contribute to urban shrinkage. In contrast to the prevalent definition of urban shrinkage that links population loss to insufficient levels of economic growth, this study examines the case of Coimbra, Portugal, where something different is happening. We hypothesise that Coimbra experiences population loss due to urban policies that promote economic growth through housing speculation. We conclude that the hypothesis is valid using semi-structured interviews and document analysis as data collection methods. The identified phenomenon disproportionately affects younger and vulnerable residents, forcing them to relocate due to unaffordable housing options. However, it benefits the local authority and national government, which collaborate with global economic powers that invest in real estate to accumulate capital. The conformist and legalistic-bureaucratic nature of the Portuguese planning system, evident in Coimbra’s local authority, exacerbates the problem. We emphasise the potentially transformative impact of economic degrowth thinking on housing policy. The implications of this research question the validity of mainstream economic theory as commonly applied to urban planning.